A Productivity Management Application of the Solow Development Model by the Asian Largest Economies - Nasution, Eric J.; Hutabarat, Francis (8ISC Abstract Proceedings, 2022)
In application of the Solow development model, other Asian or non-Asian smaller economies may learn from the productivity management model design emulated by the economic development patterns of the largest Asian economies; China, India, Japan, Indonesia, and South Korea. The objective of the study was fundamentally formulated to explore the application of the economic design thinking of the Solow development model on the five Asian largest economies. Using the data envelopment analysis or DEA, the study sought to evaluate the two Solow development models, y/L = f (K/L, L/pop, s/y) or y/Lt = K/Lt (R&Dt) 1-depr without using technology, and y/L = f (K/L, L/pop, s/y, R&D/y) or y/Lt = K/Lt (R&Dt Lt) 1-depr with technology. The DEA observation specifically applied the Malmquist Productivity Index and Linier Programming model to evaluate the y/L objective function in order to answer the study’s four research questions. It was concluded that the Solow development design thinking models, the ones with and without R&D for innovation, didn’t show any difference in utilities of both. Any economies for the productivity management models seemed to be relevantly indifferent. Keywords : Data Envelopment Analysis or DEA, Malmquist Productivity Index or MPI, change in total factor productivity or Δ TFP index, decision-making unit or DMU, linier programming or LP, human development index or HDI.